Coastal Erosion Vulnerability in Mainland China Based on Fuzzy Evaluation of Cloud Models - Cao, Chao; Cai, Feng; Qi, Hongshuai; Liu, Jianhui; Lei, Gang; Zhu, Kai; Mao, Zijian (Frontiers in Marine Science, 2022)
Global climate change-induced sea-level rise and storm wave intensification, along with the large population densities and high-intensity human development activities in coastal areas, have caused serious burden and damage to China's coasts, led to the rapid growth of artificial shorelines development, and formed a "new Great Wall" of reinforced concrete against the laws of nature. After the last ice age, transgression formed the different features of China’s coast. Depending on the types of geological and landform features, coasts are divided into 36 evaluation units, and 10 indicators are selected from natural aspects (including tectonics, geomorphology, sediment, and storms) and aspects of social economy (population, GDP, Gross Domestic Product), and cloud model theory is used to build a coastal erosion vulnerability evaluation index system in China. The results show that high grade (V), high-middle grade (IV), middle grade (III), low-middle grade (II) and low grade (I) coastal erosion vulnerability degrees account for 5.56%, 13.89%, 41.67%, 33.33% and 5.56% of the Chinese coastlines, respectively. The coastal erosion vulnerability of the subsidence zone is significantly higher than that of the uplift zone. Reverse cloud model and analytic hierarchy process calculation show that the main factors that control coastal erosion vulnerability since the transgression after the last ice age are geological structure, topography and lithological features, and in recent years, the decrease in sea sediment loads and increase in reclamation engineering. Mainland China must live with the basic situation of coastal erosion, and this study shows that the index system and method of cloud modeling are suitable for the evaluation of the coastal erosion vulnerability of the Chinese mainland. This study provides a scientific basis for the adaptive management of coastal erosion, coastal disaster assessment and the overall planning of land and sea.